A study on vessel fatigue damage as a criterion for heading selection by application of 2D actual bimodal and JONSWAP wave spectra. (15th April 2021) - Guachamin-Acero, Wilson; Portilla-Yandún, Jesús
Abstract: Planning and execution of marine operations requires proper estimation of vessel dynamic responses and their corresponding operational limits, including considerations of fatigue damage. Current guidelines for marine operations are based on a design wave height without considering the wave energy distribution in frequency and direction. This can be critical for ships operating in open seas where multimodal wave spectra may occur frequently. This study provides criteria for heading selection, with the aim of reducing fatigue damage of vessels under action of directional (2D) bimodal and multimodal wave spectra. In addition, some consequences of using analytical 2D JONSWAP spectra are also addressed. Based on a hydrodynamic model of a vessel, stresses at the midships section are computed using a spectral method. For bimodal wave spectra and considering that all dynamic responses are acceptable, fatigue damage can be reduced in about 50% when the vessel is heading to the least energetic wave component of 2D wave spectra. Moreover, fatigue damage obtained from actual 2D bimodal spectra can be well represented by its corresponding JONSWAP counterpart computed from the spectral parameters of the largest wave component. These findings can be used for vessel heading selection during planning and execution of marine operations. Highlights: Fatigue damage can be an additional criterion for heading selection of a vessel exposed to 2D bimodal wave spectra. A strategy considers heading a vessel towards specific directions of wave components. Fatigue damage can be significantly different (up to 50%) depending on the heading strategy. The capability of 2D JONSWAP spectra is assessed for cases where actual 2D wave spectra are not available. This paper provides tools to assist decision-making during execution of operations.